2010
DOI: 10.1007/s00253-010-2507-5
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning and characterization of a novel metagenome-derived multicopper oxidase with alkaline laccase activity and highly soluble expression

Abstract: Lac591, a gene encoding a novel multicopper oxidase with laccase activity, was identified through activity-based functional screening of a metagenomic library from mangrove soil. Sequence analysis revealed that lac591 encodes a protein of 500 amino acids with a predicted molecular mass of 57.4 kDa. Lac591 was overexpressed heterologously as soluble active enzyme in Escherichia coli and purified, giving rise to 380 mg of purified enzyme from 1 l induced culture, which is the highest expression report for bacter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
52
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(56 citation statements)
references
References 36 publications
4
52
0
Order By: Relevance
“…Currently, only fungal laccases are commercially exploited, but an increasing amount of evidence suggests that bacterial laccases have important properties that could compensate for their relatively low redox potential. Even without considering the ease of manipulation and expression of bacterial genes, laccases from bacteria are interesting since they are often highly active at elevated temperatures (Martins et al 2002;Miyazaki 2005) and in neutral or alkaline conditions (Reiss et al 2011;Singh et al 2007;Ye et al 2010;Zheng et al 2011;Sondhi et al 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, only fungal laccases are commercially exploited, but an increasing amount of evidence suggests that bacterial laccases have important properties that could compensate for their relatively low redox potential. Even without considering the ease of manipulation and expression of bacterial genes, laccases from bacteria are interesting since they are often highly active at elevated temperatures (Martins et al 2002;Miyazaki 2005) and in neutral or alkaline conditions (Reiss et al 2011;Singh et al 2007;Ye et al 2010;Zheng et al 2011;Sondhi et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Recent reports of highly pH-tolerant bacterial laccases (Reiss et al 2011;Singh et al 2007;Ye et al 2010;Zheng et al 2011;Sondhi et al 2014) highlight the importance of studying these enzymes in more depth. While broad approaches such as metagenomics may prove successful in finding novel laccases (Ye et al 2010), focused bioinformatic studies (Ausec et al 2011b) and on-line databases (Sirim et al 2011) suggested that potentially interesting laccase genes may be mined from putative laccase-encoding organisms.…”
Section: Introductionmentioning
confidence: 98%
“…As shown in Table 2, the reaction conditions of MCO activity are very diverse among different microbes (Ye et al 2010;Ausec et al 2015;Yang et al 2016;Safary et al 2016). However, rare forms of MCO show acidophilic properties and accordingly our results of P. hauseri MCO had optimal activity at pH 2.2.…”
Section: Mco-lacb Characterizationmentioning
confidence: 99%
“…It is expected that many more novel bacterial alkaline laccases, like Ochrobactrum sp. 531 MCO, B. halodurans Lbh1 [14], and the metagenome-derived Lac591 [29], will emerge from prokaryotic sources in near future. Unusual properties of bacterial laccases will draw more attention by industry for large scale production, green chemistry, biotechnology, and environment engineering.…”
Section: Kinetic Parameters Of Ochrobactrum531 Mcomentioning
confidence: 99%